Inverse parameter identification of elastic and inelastic constitutive material models - Hrairi, Meftah (IIUM Press, 2011)
Formulating the complete description of a material behavior includes finding the numerical values of parameters involved in its constitutive equations [I]. Traditionally, this is based on running some experimental tests and manipulating their results in order to extract the values of these parameters [2]. This chapter presents an alternative approach, based on inverse problems, which will provide a numerical method for determining accurate material parameters. This numerical tool combines an optimization algorithm with a finite element solver giving the material response to arbitrary loading. Two numerical examples are used to demonstrate the effectiveness of the developed identification technique